Cell Balancing On Three- Cell Lithium Polymer Batteries Connected In Series - Erika Loniza; Johanes Andriano Situmorang; Adha Imam Cahyadi (Universitas Muhammadiyah Yogyakarta, 2017)
Electric vehicle becomes popular recently, particularly in Indonesia. One of the most important and crucial components in an electrical vehicle is the battery. BMS (Battery Management System) is a system to monitor and regulate the performance of the battery resulting in effective-efficient-durable performance. Usually, BMS is needed to prevent battery from system failure. One of the problems that normally happens in a multi-cell battery and causing system failure is voltage unbalance. In this study, the system is designed so it can monitor the voltage condition of the three battery’s cells in series circuit and manage to balances it. The process of balancing the value of the voltage at the battery cells is known as cell balancing. The method used in this study is by using passive shunt resistor balancing method. In this method, an electronic circuit is designed in order to balance the value of the voltage at the battery cells using resistors to remove excess voltage. The result shows that the electrical circuit is capable to balance the voltage of each cell. Moreover, the designed circuit is monitored by software so it can perform in flexible manner.